The Oath-Taking (BAIAT) Phenomenon of Sampang Shia Become Sunni from A Human Rights Perspective - Ahmad Muhlis; Abd Hannan (Islam Realitas: Journal of Islamic and Social Studies, 2023)
This study discusses the integration of Sampang Shia followers into the Sunni sect from the Human Rights perspective. There are two formulations of the problem discussed in this study: what is the reality of the religious life of Sampang Shia adherents in Madura? Does the initiation of Shia Sampang contradict the principles of freedom of religion, especially the legal principles of human rights? This study uses a type of qualitative research. There are primary and secondary sources and data in this study. By using an analysis based on the perspective of legal sociology, this study found that Sampang Shia adherents experienced much unexpected problems such as intimidation, expulsion, and coercion to their religious life. Even though Sampang Shia adherents have taken allegiance to become Sunnis, they are still feeling worried and afraid. The stigma of being a former Shia adherent makes their existence and religious activities often come under scrutiny and suspicion. From the perspective of democracy in Indonesia, the series of events that have occurred in the religious life of the Shia followers of Sampang has violated the law, as contained in Article 28E paragraph (1) and Article 29 paragraph (2). Besides that, it is contrary to the principles of human rights, especially human rights principles at the personal level related to freedom of religion.Studi ini fokus membahas fenomena pembaitan pengikut syiah Sampang ke dalam aliran Sunni ditinjau dari perspektif Hak Asasi Manusia (HAM). Terdapat dua rumusan masalah yang dibahas dalam kajian ini, bagaimana realitas kehidupan beragama penganut syiah Sampang di Madura? Adakah pembaitan Syiah Sampang bertentangan dengan prinsip kebebasan beragama, terkhusus prinsip hukum Hak Asasi Manusia? Studi ini menggunakan jenis penelitian kualitatif. Sumber dan jenis data dalam penelitian ini terdiri dari dua, primer dan sekunder. Dengan menggunakan analisa berdasarkan perspektif sosiologi hukum, studi ini mendapati temuan bahwa realitas kehidupan beragama muslim syiah Sampang Madura mengalami banyak perlakuan negatif seperti intimidasi, pengusiran, dan pemaksaan. Bahkan meski sudah melakukan baiat diri menjadi Sunni, mereka (Syiah Sampang) masih dilanda rasa kekhawatiran dan ketakutan. Stigma sebagai eks penganut Syiah membuat keberadaan dan aktivitas beragama mereka sering kali mendapat sorotan dan kecurigaan. Dalam perspektif demokrasi di Indonesia, rangkaian pristiwa yang menimpa khidupan beragama penganut syiah Sampang bukan saja telah melanggar perundangan, sebagaimana termuat alam pasal 28E ayat (1) dan Pasal 29 Ayat (2). Lebih dari itu, juga bertentangan dengan prinsip Hak Asasi Manusia (HAM), khususnya prinsip HAM di level personal yang terkait dengan kebebasan beragama.